Ultraviolet nonlinear optical crystal material as well as preparation method and application thereof

By using Zn(C5H4NO)2 as the ultraviolet nonlinear optical crystal material, the [ZnN2O2] tetrahedron is formed through the coordination reaction of 4-hydroxypyridine and Zn2+, which solves the problem of poor stability of existing materials, and achieves high-efficiency response and long-life phosphorescence effect, which is suitable for applications in a variety of nonlinear optical fields.

CN119553371AActive Publication Date: 2025-03-04WUHAN TEXTILE UNIV

Patent Information

Application Number
CN202411645526.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-04
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The environmental stability, thermal stability and water resistance of existing ultraviolet nonlinear optical crystal materials limit their development in the field of laser technology.

Method used

Zn(C5H4NO)2 is used as the ultraviolet nonlinear optical crystal material. It is composed of 4-hydroxypyridine and Zn2+ through coordination bonds to form the [ZnN2O2] tetrahedron, with a regular lattice-shaped two-dimensional layer structure and high band gap, and its stability is improved through a specific preparation method.

Benefits of technology

It realizes the efficient response of ultraviolet nonlinear optical crystal materials, with SHG intensity reaching 13.6×KDP, phosphorescence life up to 558ms, and has good thermal stability, environmental stability and water resistance. It is suitable for applications in a variety of nonlinear optical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553371A_ABST
    Figure CN119553371A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nonlinear optical materials, and relates to an ultraviolet nonlinear optical crystal material and a preparation method and application thereof. The chemical formula of the ultraviolet nonlinear optical crystal material is Zn (C5H4NO) 2, C5H4NO represents 4-hydroxypyridine, and the 4-hydroxypyridine and Zn < 2 + > are combined through a coordinate bond to form a [ZnN2O2] tetrahedron; the crystal belongs to an orthorhombic system, and the space group is Fdd2. The band gap of the ultraviolet nonlinear optical crystal material is 4.40 eV, the second harmonic generation is as high as 13.6 * KDP, the birefringence delta n = 0.073 at the wavelength of 532 nm, the birefringence delta n = 0.074 at the wavelength of 1064 nm, and the ultraviolet nonlinear optical crystal material presents a photoluminescence characteristic, and has phosphorescence with the service life of 558 ms and blue afterglow visible to naked eyes and as long as 5 s under exciting light with the wavelength of 330-420 nm. In addition, the ultraviolet nonlinear optical crystal material has very strong water resistance, thermal stability and environmental stability, and has a good application prospect in the field of nonlinear optical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonlinear optical materials, and in particular to an ultraviolet nonlinear optical crystal material and a preparation method and application thereof. Background Art

[0002] Ultraviolet nonlinear optical crystal materials are a type of material that has nonlinear optical effects in the ultraviolet region, and they play an important role in the field of optoelectronic information functions. Ultraviolet nonlinear optical crystal materials are required to have a nonlinear optical effect greater than 1 times that of potassium dihydrogen phosphate crystals (1×KDP), a band gap greater than 4.2eV, and a moderate birefringence (Δn) for phase matching. In the prior art, ultraviolet nonlinear optical crystal materials have poor environmental stability, poor thermal stability, and poor water resistance, which limits their development in the field of laser technology. Summary of the invention

[0003] The invention provides an ultraviolet nonlinear optical crystal material and a preparation method and application thereof, so as to solve the problems of poor environmental stability, poor thermal stability, poor water resistance and the like of the ultraviolet nonlinear optical crystal material in the related art.

[0004] The technical solution provided by the present invention is specifically as follows:

[0005] In the first aspect, the present invention provides an ultraviolet nonlinear optical crystal material, the crystal chemical formula of which is Zn(C5H4NO)2, C5H4NO represents 4-hydroxypyridine, 4-hydroxypyridine and Zn 2+ [ZnN2O2] tetrahedron is formed by coordination bonds; the crystal belongs to the orthorhombic crystal system and the space group is Fdd2.

[0006] 4-Hydroxypyridine and Zn 2+ Combine according to the following structure:

[0007]

[0008] In combination with the first aspect of the present invention, in some embodiments, the ultraviolet nonlinear optical crystal material has a regular lattice-like two-dimensional layer structure, and the atomic arrangements of the [ZnN2O2] tetrahedrons on the same two-dimensional layer are consistent, and the atomic arrangements on different two-dimensional layers are consistent.

[0009] In conjunction with the first aspect of the present invention, in some embodiments, the unit cell parameters of the crystal are: α=90°, β=90°, γ=90°, Z=8.

[0010] In conjunction with the first aspect of the present invention, in some embodiments, the band gap of Zn(C5H4NO)2 is 4.40 eV.

[0011] In combination with the first aspect of the present invention, in some embodiments, the birefringence index of Zn(C5H4NO)2 at a wavelength of 532nm is Δn=0.073, and the birefringence index at a wavelength of 1064nm is Δn=0.074.

[0012] In combination with the first aspect of the present invention, in some embodiments, the ultraviolet nonlinear optical crystal material has phosphorescence and blue afterglow under excitation light with a wavelength of 330-420 nm.

[0013] In a second aspect, the present invention provides a method for preparing an ultraviolet nonlinear optical crystal material, comprising the following steps: preparing a crystalline material by mixing 4-hydroxypyridine and Zn 2+ The 4-hydroxypyridine and the zinc source are mixed uniformly at a molar ratio greater than 2, and the mixture is kept at 155-200° C. for at least 72 hours. After cooling, the unreacted product is washed away to obtain an ultraviolet nonlinear optical crystal material.

[0014] In conjunction with the second aspect of the present invention, in some embodiments, 4-hydroxypyridine and Zn 2+ The molar ratio is 5:1-2; and / or the zinc source is ZnF2; and / or the insulation temperature is 180°C±10°C; and / or the unreacted products are washed away with alcohol and / or water.

[0015] In a third aspect, the present invention provides applications of the above-mentioned ultraviolet nonlinear optical crystal material in the field of nonlinear optics.

[0016] In combination with the third aspect of the present invention, in some embodiments, the applications include deep ultraviolet laser lithography, semiconductor chip defect detection, shortwave communication, high-density storage, biological tissue imaging, laser micromachining, military confrontation, and environmental monitoring.

[0017] Compared with the prior art, the above technical solution provided by the embodiment of the present invention has the following advantages:

[0018] 1. The present invention is the first to increase the second harmonic generation response of zinc-based metal organic complex ultraviolet nonlinear optical crystal materials to 13.6×KDP, which is much higher than other zinc-based metal organic complex ultraviolet nonlinear optical crystal materials.

[0019] 2. The room temperature phosphorescence lifetime of the ultraviolet nonlinear optical crystal material provided by the present invention is as long as 558ms, far exceeding the existing metal-based phosphorescent materials. In addition, the ultraviolet nonlinear optical crystal material also has a long-lasting blue afterglow that is visible to the naked eye and lasts for up to 5s.

[0020] 3. The ultraviolet nonlinear optical crystal material provided by the present invention has a band gap of 4.40 eV, good thermal stability, environmental stability and water resistance, and shows stable application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 : (a) 0kl plane diffraction pattern, (b) h0l plane diffraction pattern, (c) hk0 plane diffraction pattern, and (d) unit cell structure diagram of Zn(C5H4NO)2.

[0023] Figure 2 : Crystal structure of Zn(C5H4NO)2: (a) Local coordination environment of Zn; (b) 2D planar structure (100) view; (c) (010) structure view. The polarization alignment of each Zn(C5H4NO)2 tetrahedron is indicated by a blue arrow.

[0024] Figure 3 : The development process of different coordination modes and the arrangement of each tetrahedral dipole moment in Zn(C5H4NO)2(a) (Example 1) and Zn(C5H5NO)2Cl2(b) (Comparative Example 1).

[0025] Figure 4 :Optical properties of Zn(C5H5NO)2Cl2 and Zn(C5H4NO)2: (a) Band gap values ​​of Zn(C5H5NO)2Cl2 and Zn(C5H4NO)2 obtained by Kubelka-Munk method; (b) SHG intensity of Zn(C5H4NO)2 and KDP at 1064nm laser wavelength as a function of particle size (the comparison of SHG intensity of the sample and KDP in the particle size range of 280-450nm is shown). (c) Zn(C6H8N)2SO4, Zn(C5H9NO2)2Cl2, [Zn(H-ntb)] n , Zn2(bpp)(pht)2, [Zn(bct)(H2O)2], Zn(C6H4NO2)2, Zn(S,S)C 14 H 14 N2O6、Zn(R,R)C 14 H 14 Comparison of the second harmonics of N2O6 and Zn(C5H4NO)2.

[0026] Figure 5 :(a) Electron difference density map of Zn(C5H4NO)2; (b) Theoretical SHG coefficient of Zn(C5H4NO)2; SHG weighted density of (c) virtual electron occupation density map and (d) virtual hole occupation density map in Zn(C5H4NO)2.

[0027] Figure 6 : Experimental and simulated XRD patterns of Zn(C5H4NO)2.

[0028] Figure 7 : Experimental and simulated XRD patterns of Zn(C5H5NO)2Cl2.

[0029] Figure 8 : Infrared spectrum of Zn(C5H4NO)2.

[0030] Fig. 9 : Infrared spectrum of Zn(C5H5NO)2Cl2.

[0031] Fig.10 : The refractive index of Zn(C5H4NO)2.

[0032] Fig.11 : Relative stability between Zn(C5H5NO)2Cl2 and Zn(C5H4NO)2: (a) thermal stability, and (b) water resistance.

[0033] Fig.12 : Comparison of water resistance of Zn(C5H5NO)2Cl2(a) and Zn(C5H4NO)2(b).

[0034] Fig.13 : Comparison of SHG intensity of Zn(C5H4NO)2 before and after immersion in water for 10 days (particle size: 280-450μm).

[0035] Fig.14 : Fluorescence spectrum of Zn(C5H4NO)2 (excitation wavelength 330-420nm).

[0036] Fig.15 :Phosphorescence spectrum of Zn(C5H4NO)2 (excitation wavelength 330-420nm).

[0037] Fig.16 :Zn(C5H5NO)2Cl2 decay curve (λ ex =365nm, λ em =450nm).

[0038] Fig.17 :Photoluminescence test of Zn(C5H4NO)2: (a) Normalized emission spectrum of Zn(C5H4NO)2; (b) Phosphorescence spectrum and afterglow photograph of Zn(C5H4NO)2 at 365nm; (c) λ ex =365nm and λ em=Luminescence decay of Zn(C5H4NO)2 at 420nm; (d) Temperature dependence test of Zn(C5H4NO)2; (e) Afterglow photograph of Zn(C5H4NO)2. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Unless otherwise specified, the terms used herein should be understood as the meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0041] Zinc-based metal-organic complex nonlinear optical materials have important application potential in the field of nonlinear optics, especially in light confinement, optical switching and ultrafast laser technology. However, the phosphorescence lifetime, thermal stability, environmental stability and water resistance of existing zinc-based metal-organic complex nonlinear optical materials are not ideal.

[0042] In order to solve the above problems, the present invention provides an ultraviolet nonlinear optical crystal material, whose crystal chemical formula is Zn(C5H4NO)2, C5H4NO represents 4-hydroxypyridine, 4-hydroxypyridine and Zn 2+ [ZnN2O2] tetrahedron is formed by coordination bonds; the crystal belongs to the orthorhombic crystal system and the space group is Fdd2.

[0043] 4-Hydroxypyridine and Zn 2+ Combine according to the following structure:

[0044]

[0045] The ultraviolet nonlinear optical crystal material is hereinafter referred to by the crystal chemical formula Zn(C5H4NO)2.

[0046] like Figure 2 As shown in c, the ultraviolet nonlinear optical crystal material has a regular lattice-like two-dimensional layer structure, and the atomic arrangement of [ZnN2O2] tetrahedrons on the same two-dimensional layer is consistent, and the atomic arrangement on different two-dimensional layers is consistent.

[0047] The unit cell parameters of Zn(C5H4NO)2 are: α=90°, β=90°, γ=90°, Z=8.

[0048] The band gap of Zn(C5H4NO)2 is 4.40eV, the birefringence Δn=0.073 at 532nm, and the birefringence Δn=0.074 at 1064nm. Zn(C5H4NO)2 exhibits photoluminescence properties, with a phosphorescence lifetime of 558ms under excitation light of 330-420nm, accompanied by a rare, visually perceptible, blue afterglow lasting up to 5s, and the phosphorescence lifetime is significantly extended compared to existing metal-based phosphorescent materials (see Table 5).

[0049] In addition, the SHG of Zn(C5H4NO)2 can reach 13.6×KDP, which is the highest among all zinc-based metal organic complex nonlinear optical materials. The reason is that, as shown in its structural formula, Zn(C5H4NO)2 has a coordination mode different from that of the traditional 4-hydroxypyridine ligand. 2+ The strong coordination interaction between the [ZnO2N2] and 4-hydroxypyridine ligands forces the polarizations of the [ZnO2N2] tetrahedral building units to align consistently, which results in very strong SHG, reaching 13.6 × KDP.

[0050] In addition, Zn(C5H4NO)2 has a thermal stability of up to 300°C and has excellent environmental stability and strong water resistance.

[0051] like Figure 1 As shown, non-centrosymmetric (NCS) Zn(C5H4NO)2 crystallizes in the orthorhombic system Fdd2 (no.43), and each Zn 2+ Coordinated by four heterobidentate 4-hydroxypyridine ligands, it forms a distorted [ZnN2O2] tetrahedron ( Figure 2 a), where the Zn-N bond length is The Zn-O bond length is is within the normal bond length range. At the same time, according to the charge difference density diagram ( Figure 5 a), the zinc atom in the [ZnN2O2] unit is positively charged, while the oxygen atom is negatively charged, thus polarizing the [ZnN2O2] unit. It is worth noting that (C5H4NO) - The group acts as a heterobidentate ligand, with both the pyridinic nitrogen atom and the deprotonated hydroxyl oxygen atom coordinating to the zinc. This is quite unusual and is similar to the inorganic heterobidentate ligand thiocyanate (SCN - Zn(C5H4NO)2 forms a two-dimensional layer with highly consistent orientation on the bc plane in the coordinate system ( Figure 2 b) and are closely stacked along the a-axis through edge-to-face π-π interactions. The layers stack without inversion and maintain the same orientation ( Figure 2c), which leads to all organic ring ligands (C5H4NO) - (O→N direction along the c-axis). In addition, the organic ring ligand (C5H4NO) - The rigidity is due to the planar π-conjugation effect, leading to the formation of a regular lattice-like 2D layer structure with [ZnN2O2] tetrahedra.

[0052] By calculating the dipole moments of these compounds, it was found that although the [ZnN2O2] tetrahedrons in different planes were deflected by a certain angle, the rotation axis of this deflection coincided with the direction of the dipole moment of the [ZnN2O2] tetrahedron, which resulted in this deflection not affecting the magnitude or direction (along the c-axis direction) of the dipole moment of the [ZnN2O2] tetrahedron (Table 3, Figure 3 ). This unique NCS structure produces a strong SHG effect.

[0053] Preparation method:

[0054] The invention provides a method for preparing a UV nonlinear optical crystal material, comprising the following steps: 2+ The 4-hydroxypyridine and the zinc source are mixed uniformly at a molar ratio greater than 2, and the mixture is kept at 155-200° C. for at least 72 hours. After cooling, the unreacted product is washed away to obtain an ultraviolet nonlinear optical crystal material.

[0055]

[0056] The present invention controls 4-hydroxypyridine and Zn 2+ The molar ratio is greater than 2, which can ensure that 4-hydroxypyridine is in excess and can react with Zn 2 + To form Zn(C5H4NO)2, in some embodiments of the present invention, the molar ratio of 4-hydroxypyridine to ZnF2 is 5:1 to 2. The zinc source is preferably ZnF2, and after the reaction, unreacted 4-hydroxypyridine is removed by washing with water or ethanol.

[0057] The present invention controls the reaction temperature within the range of 155-200° C., which can ensure that 4-hydroxypyridine melts without carbonization and decomposition. After melting, 4-hydroxypyridine reacts with ZnF2 to form a complex structure 1.

[0058] The Zn(C5H4NO)2 provided by the present invention is synthesized by a low temperature solid phase method as shown in formula (1), and the yield is 83.5% (calculated as zinc). During the reaction, the raw material 4-hydroxypyridine (compound 3) loses hydroxyl hydrogen at high temperature, and generates intermediate 4 and HF under the action of zinc fluoride. Then, intermediate 4 has two active sites that react with Zn 2+The coordination forms the complex structure 1, namely Zn(C5H4NO)2. The complex structure 1 is well resolved by advanced three-dimensional precision electron diffraction tomography technology (Table 1). By analyzing the diffraction patterns of the 0kl, h0l and hk0 planes and the reconstructed dynamic refinement patterns, the positions of all C, H, O, N, and Zn atoms are determined, and the structure is finally well determined ( Figure 1 ). Powder X-ray diffraction data confirmed the phase identity and purity, and the fully assigned experimentally observed PXRD pattern also confirmed the accuracy of the 3D ED structure refinement.

[0059] application:

[0060] The ultraviolet nonlinear optical crystal material Zn(C5H4NO)2 provided by the present invention has good thermal stability at 300°C, excellent environmental stability and strong water resistance, and has good application prospects in the field of nonlinear optics, such as deep ultraviolet laser lithography, semiconductor chip defect detection, shortwave communication, high-density storage, biological tissue imaging, laser micromachining, military confrontation, and environmental monitoring.

[0061] Example:

[0062] The ultraviolet nonlinear optical crystal material and the preparation method thereof provided by the present invention are described in detail below through specific embodiments:

[0063] In order to compare the structure and performance, Example 1 of the present invention synthesized Zn(C5H4NO)2 by a low temperature solid phase method, and the reaction formula is shown in Formula (1). Comparative Example 1 synthesized the centrosymmetric compound Zn(C5H5NO)2Cl2 by a hydrothermal method. The main difference between the two is that the coordinating atoms around Zn are different. It is found that Zn(C5H5NO)2Cl2 and Zn(C5H4NO)2 both use 4-hydroxypyridine as a ligand but exhibit completely different structures and properties. The applicant found that in the synthesis of Zn(C5H5NO)2Cl2, 4-hydroxypyridine (Compound 3) first removes H from the hydroxyl group. + The intermediate 4 is obtained, and then the N atom in the intermediate 4 reacts with the water in the system to obtain a protonated compound, which undergoes structural intercalation to form Zn(C5H5NO)2Cl2. Since Zn(C5H5NO)2Cl2 has only one active site, it is formed with ZnCl2, and its structure is completely different from that of Zn(C5H4NO)2 ( Figure 3 ). In Zn(C5H5NO)2Cl2(C2 / c, no.15), Zn 2+ [ZnO2Cl2] tetrahedron is formed, and the main Zn-O, CO and CN bond lengths are consistent with Zn(C5H4NO)2.

[0064] The Kubelka-Munk method was used to calculate the band gaps of Zn(C5H5NO)2Cl2 and Zn(C5H4NO)2 and explore their potential for applications in the UV range, such as Figure 4 As shown in (a), the band gap of Zn(C5H4NO)2 is 4.40 eV, which is larger than the band gap of Zn(C5H4NO)2Cl2 4.11 eV, indicating that it has a wide light transmittance range in the UV range, indicating its potential application potential in the UV range.

[0065] The present invention calculates the linear and nonlinear optical properties of Zn(C5H4NO)2 and finds that: Δn of Zn(C5H4NO)2 cal .=0.073@532nm and Δn cal. =0.074@1064nm, which is moderate and meets the phase matching condition of ultraviolet nonlinear optical materials ( Fig.10 ).

[0066] The present invention uses the Kurtz-Perry powder SHG test method and uses the benchmark KDP material as a reference to measure the SHG intensity of Zn(C5H4NO)2 at 1064nm. Figure 4 As shown in (b), the SHG intensity increases with the increase of particle size and reaches a plateau in the range of 280–450 μm, indicating that phase matching can be achieved.

[0067] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. Zinc fluoride (ZnF2, 99%, Maclean), zinc chloride (ZnCl2, 99%, Maclean), and 4-hydroxypyridine (C5H5NO, 99%, Maclean) used in the embodiments of the present invention were used directly without further purification.

[0068] The following are the characterization methods of the materials:

[0069] (1) 3D ED by electron diffraction tomography (PEDT):

[0070] The Zn(C5H5NO)2 polycrystalline sample was ground and then transferred to a test tube, ultrasonically treated in anhydrous ethanol for 5 minutes, then dropped on a copper grid coated with a carbon film and dried in air for 5 minutes. PEDT 3D ED data were collected on a FEI Tecnai G2F20 transmission electron microscope (200kV) equipped with a Gatan 832 camera. The processing speed was 100Hz and the exposure time per frame was 2s. The data reduction was processed using the PETS2.0 program. The structure was determined from scratch using the charge flip algorithm in the Superflip program. Dynamic refinement of the PEDT data was completed in the program.

[0071] (2) Single crystal X-ray diffraction:

[0072] Single crystal X-ray diffraction (SC-XRD) data of Zn(C5H5NO)2Cl2 samples were collected on an XtaLAB Synergy R equipped with a graphite monochromator using Mo Kα radiation. was performed at 298 K. The crystal structure was solved by the direct method of Olex2 and refined by the least-squares technique of anisotropic thermal parameters of all atoms.

[0073] (3) Powder X-ray diffraction (PXRD):

[0074] Powder X-ray diffraction data were recorded on an Advance diffractometer at 40 kV, 100 mA, Cu Kα1 radiation (Bruker D8, radiation wave number 1.5406 A), a scan rate of 10° / min, and a scan angle range of 10-70°. Phase purity was determined by powder X-ray diffraction.

[0075] (4) Infrared spectroscopy

[0076] IR spectra were collected on a Nicolet iS5 Fourier transform infrared spectrometer in the wavelength range of 4000–400 cm at room temperature. -1 The sample and dry KBr were mixed at a weight ratio of 1:100 and ground into flakes for measurement.

[0077] (5) UV-Vis diffuse reflectance spectroscopy

[0078] UV-Vis diffuse reflectance spectra were obtained at room temperature using a Varian Cary 5000 spectrophotometer with a scan range of 200-800 nm. Spectrally pure barium sulfate was selected as a reference (100% reflectance) and the ground powder sample was coated on its surface for testing.

[0079] (6) Phosphorescence spectrum

[0080] The phosphorescence excitation spectra and luminescence emission decays of the samples were obtained using a Hitachi F-4700 spectrophotometer.

[0081] (7) Thermal analysis

[0082] Thermogravimetric analysis (TGA) was performed using a Netzsch STA449F5 analyzer. The specific method was to weigh about 0.8 mg of sample, put it into a platinum crucible, and heat it at 10 K min in a N2 gas atmosphere. -1 The rate of heating is from room temperature to 800°C.

[0083] (8) Second harmonic generation measurement

[0084] Second-order nonlinear optical measurements were performed on powder samples at room temperature, and the SHG effect of the powder samples was measured using a Q-switched 1064nm Nd:YAG laser using a modified Kurtz and Perry method. Polycrystalline samples of the compound were screened into different particle sizes (35-50, 50-74, 74-100, 100-154, 154-180, 180-280 and 280-450μm) to investigate whether their SHG responses can be phase matched. A reference material KH2PO4 (KDP) was selected to compare the SHG efficiency of the samples to evaluate the second-order NLO effect of the measured samples.

[0085] (9) Calculation method

[0086] The first-principles calculations of Zn(C5H4NO)2 were based on the CASTEP module of the Materials Studio software package, and the system geometry was optimized by density functional theory. The exchange-correlation functional was described by the generalized gradient approximation Heyd-Scuseria-Ernzerhof (HSE06), the cutoff energy was set to 550 eV, and a Monkhorst-Pack k-point grid of 3×3×3 was selected in the first Brillouin zone to ensure the accuracy of the calculation results. The self-consistent iterative convergence (SCF) was 5.0×10 -7 eV / atom, the maximum displacement converges to The internal stress is 0.1 GPa and the force on the atoms is The energy converges to 2.0×10 -6 eV / atom. The ion-electron interaction of all atoms is modeled by an ultrasoft pseudopotential, and the atomic electronic configuration is: C(2s 2 2p 2 ), H(1s 1 ), N(2s 2 2p 3 ), O(2s 2 2p 4 ), Zn(3d 10 4s 2 ).

[0087] Example 1: Low temperature solid phase method synthesis of compound Zn(C5H4NO)2:

[0088] ZnF2 (1mmol, 0.103g) and 4-hydroxypyridine (crystal chemical formula is C5H5NO, 5mmol, 0.475g) were ground and mixed in an agate mortar for 5min to mix evenly, and then the mixture was transferred to a polytetrafluoroethylene-lined reactor. The reactor was heated to 180°C in an oven and maintained for 72h, and then slowly cooled to 30°C at a rate of 3°C / h. The resulting product was repeatedly sonicated with deionized water and anhydrous ethanol to obtain white powdery Zn(C5H4NO)2 crystals (the yield based on Zn was 83.5%).

[0089] Comparative Example 1: Synthesis of compound Zn(C5H5NO)2Cl2 by simple hydrothermal method:

[0090] In order to compare the structure and properties of Zn(C5H4NO)2, this comparative example prepared a centrosymmetric compound Zn(C5H5NO)2Cl2 closely related to Zn(C5H4NO)2:

[0091] ZnCl2 (1 mmol, 0.136 g), 4-hydroxypyridine (2 mmol 0.172 g) and 3 mL of deionized water were added to a hydrothermal reactor, the temperature was raised from room temperature to 150 ° C, kept for 24 hours, and then slowly cooled to room temperature at a rate of 5 ° C / h to obtain colorless block-like Zn(C5H5NO)2Cl2 crystals (the yield based on Zn was 75.5%).

[0092] Characterization and results:

[0093] The samples obtained in Example 1 and Comparative Example 1 were characterized, and the results were as follows:

[0094] Table 1 Crystallographic data of samples prepared in Example 1

[0095]

[0096]

[0097] It can be seen from Table 1 that the crystal chemical formula of the sample prepared in Example 1 can be expressed as Zn(C5H4NO)2, the crystal structure is orthorhombic, the space group is Fdd2 (no.43), and the unit cell parameters are: α=90°, β=90°, γ=90°, Z=8.

[0098] Table 2 Atomic coordinates and equivalent isotropic displacement parameters and occupancy of Zn(C5H4NO)2 prepared in Example 1

[0099]

[0100] Table 3Zn(C5H4NO)2, Zn(C5H5NO)2Cl2, C5H5NO, C5H4NO - 、C5H5NO calculated dipole moment component

[0101]

[0102]

[0103] Table 4 Crystal data and structure refinement of Zn(C5H5NO)2Cl2 of the sample prepared in Comparative Example 1

[0104]

[0105] As shown in Table 4, the crystal chemical formula of the sample prepared in Comparative Example 1 of the present invention can be expressed as Zn(C5H5NO)2Cl2. At the same time, it can be seen from the crystal data that Zn(C5H4NO)2 prepared in Example 1 and Zn(C5H5NO)2Cl2 prepared in Comparative Example 1 both use 4-hydroxypyridine as a ligand, but show completely different structures and properties.

[0106] Table 5 Comparison of phosphorescence lifetime of Zn(C5H4NO)2 and reported metal-based phosphorescent materials

[0107]

[0108] As can be seen from Table 5, the phosphorescence lifetime of Zn(C5H4NO)2 prepared by the present invention far exceeds that of the reported metal-based phosphorescent materials. Due to the long emission lifetime of phosphorescent materials, they can continue to emit light after the excitation stops, and the short-lived fluorescence interference can be eliminated, so that they can still be clearly displayed in an environment with strong background light or fluorescence interference, providing a higher signal-to-noise ratio, which is particularly important for applications requiring high contrast and clarity, such as bioimaging and information encryption. In addition, this performance is also very useful in anti-counterfeiting markings and security applications, and can be used in advanced anti-counterfeiting and encryption fields. Since the long life can provide a more stable light source, Zn(C5H4NO)2 also has application potential in LED lighting and laser technology. Compared with traditional metal-based phosphorescent materials, the Zn(C5H4NO)2 provided by the present invention has the characteristics of low toxicity, low cost and high flexibility, which makes them show great application prospects in many fields.

[0109] like Figure 4As shown in (b), the SHG intensity of Zn(C5H4NO)2 increases with the increase of particle size and reaches a platform in the particle size range of 280-450μm, satisfying the phase matching condition. Specifically, the maximum SHG intensity of Zn(C5H4NO)2 is 13.6 times that of KH2PO4, which is the strongest among the recently reported zinc-based metal complex ultraviolet nonlinear optical crystal materials ( Figure 4 c).

[0110] like Fig.11 As shown in a, Zn(C5H4NO)2 exhibits excellent thermal stability and does not decompose significantly below 300°C. Fig.11 b and Fig.12 It was shown that the structural integrity of Zn(C5H4NO)2 remained unchanged after exposure to ambient air and humidity for up to 6 months, with no obvious degradation or deliquescence. The inventors further experimentally studied the water resistance of Zn(C5H4NO)2 and Zn(C5H5NO)2Cl2 and found that Zn(C5H5NO)2Cl2 dissolved rapidly in water and completely dissolved in about 10 minutes, while Zn(C5H4NO)2 remained insoluble after being immersed in water for 10 days. The inventors analyzed that Zn(C5H4NO)2 is insoluble in water because it has a polar structure. In addition, it is worth noting that Fig.13 As shown, the SHG intensity of Zn(C5H4NO)2 did not change after being immersed in 1064nm laser irradiation for 10 days, indicating that it has stable performance in extreme environments and high potential application value.

[0111] like Fig.17 As shown in e, Zn(C5H4NO)2 exhibits photoluminescence properties, emitting blue light for 5s after being excited by 365nm ultraviolet light. It has emission peaks at 440nm and 420nm ( Fig.14 , Fig.15 , Fig.17 b). TRPL shows that the lifetime of Zn(C5H4NO)2 is 588ms and that of Zn(C5H5NO)2Cl2 is 183ms ( Fig.16 , Fig.17 c), which is the longest among zinc-based semi-organic crystals (Table 5). Fig.16 a) and temperature-dependent photoluminescence (PL) studies ( Fig.17 d), delayed fluorescence (DF) may exist in Zn(C5H4NO)2.

[0112] Using first-principles calculations in CASTEP in Materials Studio, Zn(C5H4NO)2 has significant π-π stacking between its organic rings A and B, with a distance of The HOMO mainly comes from the (C5H4NO)-π orbital, while the LUMO comes from the π* orbital. This interaction enhances the spin-orbit coupling and improves the luminescence efficiency of the compound.

[0113] Theoretical calculations show that Zn(C5H4NO)2 has a direct band gap of 4.38 eV, which is in good agreement with the experimental result of 4.40 eV. DOS and PDOS analysis reveal that the conduction band is mainly composed of C-2p, N-2p and O-2p states, and the valence band is mainly composed of N-2p, O-2p and C-2p orbitals, with minimal participation of Zn-3d. - The interaction between the CO bond in the ring and the CC and CN bonds and the ring and Zn 2+ interaction effects.

[0114] The second-order nonlinear optical coefficient (d ij ) is calculated as d at 1064nm (1.165eV) 31 =9.71,d 32 = 21.7, and d 33 =16.52×10 -9 pm / V. KDP 36 The value is 0.39pm / V( Figure 4 b), calculated d 32 It is 21.7 times that of KDP.

[0115] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. An ultraviolet nonlinear optical crystal material, characterized in that: The crystal chemical formula is Zn(C5H4NO)2, C5H4NO represents 4-hydroxypyridine, 4-hydroxypyridine and Zn 2+ [ZnN2O2] tetrahedron is formed by coordination bonds; the crystal belongs to the orthorhombic system and the space group is Fdd2.

2. The ultraviolet nonlinear optical crystal material according to claim 1, characterized in that: The ultraviolet nonlinear optical crystal material has a regular lattice-like two-dimensional layer structure, and the atomic arrangement of the [ZnN2O2] tetrahedron is consistent on the same two-dimensional layer and on different two-dimensional layers.

3. The ultraviolet nonlinear optical crystal material according to claim 1, characterized in that: The unit cell parameters of the crystal are: α=90°, β=90°, γ=90°, Z=8.

4. The ultraviolet nonlinear optical crystal material according to claim 1, characterized in that: The band gap of Zn(C5H4NO)2 is 4.40 eV.

5. The ultraviolet nonlinear optical crystal material according to claim 1, characterized in that: The birefringence index of Zn(C5H4NO)2 at a wavelength of 532nm is Δn=0.073, and the birefringence index at a wavelength of 1064nm is Δn=0.

074.

6. The ultraviolet nonlinear optical crystal material according to claim 1, characterized in that: The ultraviolet nonlinear optical crystal material has phosphorescence and blue afterglow under the excitation light with a wavelength of 330-420nm.

7. A method for preparing an ultraviolet nonlinear optical crystal material, characterized in that: The process comprises the following steps: 2+ The 4-hydroxypyridine and the zinc source are mixed uniformly at a molar ratio greater than 2, and the mixture is kept at 155-200° C. for at least 72 hours. After cooling, the unreacted product is washed away to obtain an ultraviolet nonlinear optical crystal material.

8. The method for preparing the ultraviolet nonlinear optical crystal material according to claim 7, characterized in that: 4-Hydroxypyridine and Zn 2+ The molar ratio is 5:1-2; and / or, The zinc source is ZnF2; and / or, The holding temperature is 180℃±10℃; and / or, The unreacted products are washed away with alcohol and / or water.

9. Application of the ultraviolet nonlinear optical crystal material according to any one of claims 1 to 6 in the field of nonlinear optics.

10. The use according to claim 9, characterized in that: The applications include deep ultraviolet laser lithography, semiconductor chip defect detection, shortwave communications, high-density storage, biological tissue imaging, laser micromachining, military confrontation, and environmental monitoring.

Citation Information

Patent Citations

  • Fluorescent material Zn2(hfoac)4(4,4-pybi)2 and synthesis method thereof

    CN104130773A

  • Nonlinear optical crystal and preparation method and application thereof

    CN114808137A

  • Zinc nicotinate tetrahydrate birefringent crystal as well as preparation method and application thereof

    CN117626443A

Cited By

  • Hybrid metal chloride with non-centrosymmetric structure and preparation method and application thereof

    CN120329300A